Evaluation of dietary fish meal analog with or without supplementation of natural feed additives as the substitute of fish meal in juvenile Japanese eel, Anguilla japonica - Bae, Jinho; Lee, Seunghyung; Moniruzzaman, Mohammad; Hamidoghli, Ali; Choi, Wonsuk; Lee, Seunghan; Min, Taesun; Kim, Shin-Kwon; Bai, Sungchul C. (Frontiers in Marine Science, 2022)
We investigated the nine experimental diets contained with fish meal (FM) and/or fishmeal analogue (FMA) as the major source of animal protein to determine the optimum FMA level as the substitute of FM protein in the diet of juvenile Japanese eel. In addition, two natural feed additives such as song-gang stone (SG) and yucca meal (YM) were supplemented in the diet to evaluate their efficacy as the immunostimulants. The diets are: 100% FM + 0% FMA in diet (FMA0), 90% FM + 10% FMA in diet (FMA10), 80%FM+20% FMA in diet (FMA20), 70% FM + 30% FMA in diet (FMA30), 60% FM + 40% FMA in diet (FMA40), FMA0 + 0.4 % SG (FMA0SG), FMA0 + 0.1% YM (FMA0YM), FMA20 + 0.4% SG (FMA20SG) and FMA20 + 0.1% YM (FMA20YM). Nine groups of Japanese eel each with three replicates distributed (initial weight of 9± 0.2 g) in rectangular tanks receiving flow through water. Each group of the treatment consisted with 15 fish and fed one of the diets for 8 weeks. At the end of the feeding trial, fish fed the FMA0 and FMA10 diets showed no significant differences in weight gain (WG), specific growth rate (SGR), feed efficiency (FE) and protein efficiency ratio (PER). Meanwhile, fish fed FMA20, FMA30 and FMA40 diets showed significantly lower WG, SGR, FE and PER than the fish fed the FMA0 (control) diet. In addition, there were no significant difference among fish fed the SG and YM supplemented diet groups. However, lysozyme activities in fish fed the FMA10, FMA20, FMA30 and FMA40 was significantly lower than the fish fed the FMA0SG, FMA0YM, FMA20SG and FMA20YM diets. After 7 days of injection with V. Anguillarum, cumulative survival rates of fish fed the FMA0SG and FMA0YM diets were significantly higher than the FMA0 diet group. The results revealed that the FMA could replace up to 10% of FM as a protein source in the diet of Japanese eel and both of the natural feed additives (SG and YM) could improve replacing rates of FMA from 10% to 20% without compromising growth and health status of fish.